Natural capital enhances farm production, profitability and financial resilience: findings from a study on 230,000 ha of farmland in Australia - Elizabeth Heagney; Daniel Gregg; Dan Hill; James Radford; Grace Sutton; Fred Rainsford; Daniel O'Brien; Angela Hawdon; Imogen Semmler; Mark Gardner; Milly Taylor; Sue Ogilvy (Agricultural Systems, 2026)

Natural capital metrics as predictors of farm-scale richness of birds and plants - Frederick W. Rainsford; Grace J. Sutton; Sue Ogilvy; Daniel O’Brien; Imogen Semmler; Rachel Lawrence; Alex Maisey; Annette Cavanagh; William F. Mitchell; James Q. Radford (Agriculture, Ecosystems & Environment, 2025)

Partial migration pays off in black-faced cormorants: insights from post-breeding GPS tracking - Thomas Cansse; Luc Lens; Rachael A. Orben; Grace J. Sutton; Jonathan A. Botha; John P.Y. Arnould (Marine Biology, 2024)
Seasonal variation in food availability or adverse weather patterns can create challenging conditions for year-round survival. Birds experiencing such fluctuations may migrate to locations with better food availability in the non-breeding period. While some species are obligate migrants, others are facultative migrants where various post-breeding strategies exist within populations. Several cormorant and shag species are facultative migrants with a range of post-breeding movement strategies within populations. Currently, most of the information available on cormorant post-breeding strategies originates from banding studies and little is known about their movements, time budget or habitat use during the non-breeding period. In the present study, Australian endemic black-faced cormorants ( Phalacrocorax fuscescens ), breeding on Notch Island, Victoria, were tracked with GPS data loggers during the non-breeding period. Different post-breeding strategies were observed. Individuals were either resident ( N = 36, 69%), remaining within a short distance of the colony (16.7 ± 2.2 km) or migratory ( N = 16, 31%), travelling greater distances (250.7 ± 24.4 km) to establish a new central place foraging location. Data from individuals which covered the entire non-breeding period indicated that, across strategies, individual birds had one area of residency during the non-breeding period. Migratory individuals were found to have lower daily activity levels, spending less time flying and foraging, than resident individuals during the early non-breeding period, possibly indicating that they had access to greater prey resources. Regardless of the post-breeding strategy, individuals utilised foraging locations that were of similar seabed depths year-round suggesting individual specialisation in prey resources or foraging habitats.

Stage-dependent niche segregation: insights from a multi-dimensional approach of two sympatric sibling seabirds - Aymeric Fromant; John P. Y. Arnould; Karine Delord; Grace J. Sutton; Alice Carravieri; Paco Bustamante; Colin M. Miskelly; Akiko Kato; Maud Brault-Favrou; Yves Cherel; Charles-André Bost (Oecologia, 2022)
Niche theory predicts that to reduce competition for the same resource, sympatric ecologically similar species should exploit divergent niches and segregate in one or more dimensions. Seasonal variations in environmental conditions and energy requirements can influence the mechanisms and the degree of niche segregation. However, studies have overlooked the multi-dimensional aspect of niche segregation over the whole annual cycle, and key facets of species co-existence still remain ambiguous. The present study provides insights into the niche use and partitioning of two morphologically and ecologically similar seabirds, the common (CDP, Pelecanoides urinatrix ) and the South Georgian diving petrel (SGDP, Pelecanoides georgicus ). Using phenology, at-sea distribution, diving behavior and isotopic data (during the incubation, chick-rearing and non-breeding periods), we show that the degree of partitioning was highly stage-dependent. During the breeding season, the greater niche segregation during chick-rearing than incubation supported the hypothesis that resource partitioning increases during energetically demanding periods. During the post breeding period, while species-specific latitudinal differences were expected (species specific water mass preference), CDP and SGDP also migrated in divergent directions. This segregation in migration area may not be only a response to the selective pressure arising from competition avoidance between sympatric species, but instead, could reflect past evolutionary divergence. Such stage-dependent and context-dependent niche segregation demonstrates the importance of integrative approaches combining techniques from different fields, throughout the entire annual cycle, to better understand the co-existence of ecologically similar species. This is particularly relevant in order to fully understand the short and long-term effects of ongoing environmental changes on species distributions and communities. This work demonstrates the need of integrative multi-dimensional approaches combining concepts and techniques from different fields to understand the mechanism and causal factors of niche segregation.

Changing with the times: little penguins exhibit flexibility in foraging behaviour and low behavioural consistency - Elodie C. M. Camprasse; Grace J. Sutton; Maud Berlincourt; John P. Y. Arnould (Marine Biology, 2017)